2014
DOI: 10.1051/0004-6361/201321519
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical galaxy properties on Lyαescape in star-forming galaxies

Abstract: Context. Among the different observational techniques used to select high-redshift galaxies, the hydrogen recombination line Lymanalpha (Lyα) is of particular interest because it gives access to the measurement of cosmological quantities such as the star formation rate (SFR) of distant galaxy populations. However, interpreting this line and calibrating such observables are still subject to serious uncertainties. Aims. In this context, it important to understand the mechanisms responsible for the attenuation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
69
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 106 publications
24
69
1
1
Order By: Relevance
“…This behavior suggests that Lyα photons do not scatter as far in galaxies with higher dust content. This is consistent with studies that show that the Lyα escape fraction decreases with dust content (Hayes et al 2013;Atek et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…This behavior suggests that Lyα photons do not scatter as far in galaxies with higher dust content. This is consistent with studies that show that the Lyα escape fraction decreases with dust content (Hayes et al 2013;Atek et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Blanc et al (2011) report a correlation between the Ly α equivalent width and reddening in high-z LAEs. Similarly, Atek et al (2014) observe a clear dependence of the Ly α escape fraction on the dust extinction in nearby galaxies.…”
Section: Dependence On Dustmentioning
confidence: 64%
“…dust extinction, stellar mass, and metallicity These Green Peas are very well studied galaxies and provide a great opportunity to explore the dependence of Lyα escape on other galactic properties. Previous studies have found that f the relation between f Lyα esc and metallicity are unclear Atek et al 2014;Hayes et al 2014; Paper I). Our sample covers the full ranges of dust extinction and metallicity of Green Peas.…”
Section: Lyα Escape and Other Galactic Propertiesmentioning
confidence: 92%